2014
DOI: 10.1158/1055-9965.epi-13-1165
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Prostate Cancer in Lynch Syndrome: A Systematic Review and Meta-analysis

Abstract: It has been controversial that men carrying a DNA mismatch repair (MMR) gene mutation (Lynch syndrome) are at heightened risk of prostate cancer given that an increased risk is likely to be modest and the prevalence of prostate cancer is high. We used PubMed to search for "molecular studies" that reported MMR-deficiency status of prostate cancer tumors in men with an MMR gene mutation, and "risk studies" that reported prostate cancer risk for men known or suspected to have an MMR gene mutation relative to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 49 publications
1
64
0
2
Order By: Relevance
“…Several studies have demonstrated increased risk of prostate cancer with mutations in known prostate cancer susceptibility genes (Table ) . Although conventional opinion has held that the prevalence of patients with prostate cancer harboring germline alterations was quite low, recent data challenge that notion.…”
Section: Genetic Basis Of Prostate Cancer Predispositionmentioning
confidence: 99%
“…Several studies have demonstrated increased risk of prostate cancer with mutations in known prostate cancer susceptibility genes (Table ) . Although conventional opinion has held that the prevalence of patients with prostate cancer harboring germline alterations was quite low, recent data challenge that notion.…”
Section: Genetic Basis Of Prostate Cancer Predispositionmentioning
confidence: 99%
“…Several studies have found the lifetime risk for prostate cancer in Lynch syndrome to be increased by two-to five-fold 7577. Additional studies are needed to determine whether Lynch syndrome-associated prostate cancers occur at an earlier average age or are more aggressive 75,76…”
Section: Clinical Spectrum Of Lynch Syndromementioning
confidence: 99%
“…Lynch syndrome is an autosomal dominant inherited disorder of cancer susceptibility caused by a heterozygous germline mutation in one of the MMR genes [2] or a deletion in the 3' end of the EPCAM gene, which leads to epigenetic silencing of the closely linked MSH2 3]. Carriers of a heterozygous MMR gene mutation are at increased risk of multiple adult cancers, most notably colorectal and endometrial cancer, but also cancer of the stomach, ovary, ureter, renal pelvis, brain, small bowel, and hepatobiliary tract [4], as well as breast [5] and prostate [6]. The development of these cancers generally occurs in mutation carriers at a younger age than in the general population.…”
Section: Introductionmentioning
confidence: 99%